Investigação sobre a formação continuada de professores do Ensino Fundamental I: modelagem matemática - Santos, Douglas Borreio Maciel dos (2020)
The present research is part of the theme of the continuing education of teachers of the basic school, having as central point the use of mathematical modeling; was de-veloped in the Postgraduate Studies Program in Mathematical Education at PUC-SP. The guiding question was thus proposed: How do teacher training initiatives in the early years of elementary school using modeling, in Burak's perspective, contribute to the development mathematical knowledge and professional practice? She carried out the general objective: to investigate the potential of mathematical modeling as a teaching method, in the teaching practice of elementary school teachers I. It was considered as theoretical support the concepts of mathematical modeling in the classroom of Burak and supporters and precepts for a qualitative investigative research by Bogdan and Biklen. The development of the research took place in two phases: one of them diag-nosis. Used as means of data collection, questionnaires, audio, video, and photo-graphs recordings. The theoretical framework supported the development of activities in stages, the themes were defined according to the interest of the participants and with experimentation in the classroom. The diagnostic phase was important for the researcher's maturity in conducting the data consolidation phase. The experiments carried out in the classroom with the students were fundamental to bring security to the teacher and, consequently, to provide him with his own experience to take ad-vantage of the pedagogical resources arising from the use of modeling. One can refer to the advances that other research has indicated in the professional practice of teachers of elementary school I, enabling them to deal with mathematics in a less rigid way, and to assign meaning to mathematics for their students